IL-17A Modulates Peritoneal Macrophage Recruitment and M2 Polarization in Endometriosis - Miller, Jessica E.; Ahn, Soo Hyun; Marks, Ryan M.; Monsanto, Stephany P.; Fazleabas, Asgerally T.; Koti, Madhuri; Tayade, Chandrakant (Frontiers in Immunology, 2020)
Endometriosis is a debilitating gynecological disease characterized by the extrauterine presence of, endometrial-like tissues located on the peritoneal membrane and organs of the pelvic cavity. Notably, dysfunctional immune activation in women with endometriosis could also contribute to the development of disease. In particular, alternatively activated (M2) peritoneal macrophages are shown to aid peritoneal lesion development by promoting remodeling of extracellular matrix and neovascularization of lesions. However, the stimuli responsible for polarizing M2 macrophages in endometriosis remain elusive. Interleukin-17A (IL-17A) can induce M2 macrophage polarization in other disease models and IL-17A is elevated in the plasma and endometriotic lesions of women with endometriosis. In this study, we investigated whether IL-17A could induce macrophage recruitment and M2 polarization, while promoting endometriotic lesion growth through enhanced vascularization. By utilizing a co-culture of macrophage-like THP-1 cells with an endometriotic epithelial cell line, our in vitro results suggest that IL-17A indirectly induces M2 markers CCL17 and CD206 by interacting with endometriotic epithelial cells. Further, in a syngeneic mouse model of endometriosis, IL-17A treatment increased macrophages in the peritoneum, which were also M2 in phenotype. However, IL-17A treatment did not augment proliferation or vascularization of the lesion in the study time frame. These findings suggest that IL-17A may be a stimulus inducing the pathogenic polarization of macrophages into the M2 phenotype by first acting on the endometriotic lesion itself.